A graphical model for evaluating the status of series‐connected lithium‐ion battery pack. (3rd December 2018) - Feng, Xuning; Xu, Chengshan; He, Xiangming; Wang, Li; Gao, Shang; Ouyang, Minggao
Summary: State evaluation of battery pack is essential for battery management but laborious when dealing with massive information of cells within the pack. A graphical model for evaluating the status of series‐connected Li‐ion battery pack is established to release the burden. The model is founded by a 2D diagram, with the electric quantity " E " and the capacity " Q " as its axes, therefore called by the " E ‐ Q diagram." The new graphical diagram presents the dynamics of cell variations in a linear way, thereby benefiting the design and management of battery pack, including (1) quantifying the cell variations by region, (2) illustrating the evolution of cell variations during aging, (3) guiding the estimation of pack states considering algorithm error in cell states, and (4) solving the balancing problem. The experimental results conform to the theoretical analysis, indicating that the E ‐ Q diagram will be pervasively applied in the design and management of series‐connected battery pack. Moreover, the E ‐ Q diagram is suitable for education on the basics of a battery pack, because it is a graphical model. Abstract : Novelty statements: This paper builds a novel graphical model for evaluating the status of series‐connected battery pack. The model can vividly present the cell variations of a battery pack in 2D diagram, named the E‐Q diagram. Error propagation from the cell state estimation to that of the pack and strategies for cell balancing are clearly interpreted by the graphical model.